An Analysis of Onomatopoeia in a Webcomic Tower of God - Farsih Handayani; Dohra Fitrisia; Diana Achmad (Universitas Syiah Kuala, 2022)
A webcomic has become a very popular page for students today to read. Webtoon is one of the most visited comic templates. The various stories and good animation are advantages for webtoon. Tower of God season 1 is a story in a webtoon that has many readers. This is because the story is full of sensations and plays the imagination which is supported by the animation in it. In reading comics, you will find onomatopoeia words. The word onomatopoeia is the formation of a word from a sound associated with what is named. The existence of this word in comics is often overlooked because it is only skimmed by readers. Readers only focus on their imagination caused by the onomatopoeia. However, the type. Therefore, this study aims to identify the kinds of onomatopoeia used in the Webtoon “Tower of God Season 1”. It is hoped that this research setting onomatopoeia in comics is a great way to make students, as readers or audiences, interested in understanding the stories. This study uses qualitative research methods to describe the results of this study. Data collection techniques were carried out using the documentation method through data cards to classify the types and meanings of onomatopoeia words found.The results of this study show that the categorization was conducted based on the relation between verbal sound and meaning differentiated into referent, denotation, and connotation. Onomatopoeic words finding was classified into; 87 of direct onomatopoeia, 80 of associative onomatopoeia, and 91 of exemplary onomatopoeia.